VOLLEYBALL AS A TOOL OF INTEGRATION OF GENDER IN SCHOOL PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2014)
Such an assay aimed to analyze the teaching volleyball made contributions to the integration of gender in physical education classes . To deepen the study descriptors for use in research journals , scientific journals , books , and more. We conclude that volleyball is a tool that should not be dismissed by the teacher in physical education classes , however , which will be decisive for its contribution to help in the teaching- learning process of young people who practice it will be how the teacher will lead the sport because only mix boys and girls in physical education classes will not be enough to promote an educational prátiva , because this is only one strategy for ending the desiguadades .Thus , there are other factors that influence the need for targeted action and a insserção public policy co-education .
Keywords: Physical Education; volleyball; gender .